Fibrillary glomerulonephritis with a favourable prognosis of 26 years - David Micarelli; Valentina Pistolesi; Emanuela Cristi; Anna Rita Taddei; Ilaria Serriello; Santo Morabito; Konstantinos Giannakakis (Society of Diabetic Nephropathy Prevention, 2021)
Fibrillary glomerulonephritis (FGN) is a rare glomerular disease. The prognosis is usually unfavorable with nearly half of patients progressing to end-stage renal disease within 4 years. We report a case of biopsy-proven FGN characterized by an unusual benign clinical course in which a kidney biopsy, repeated after an extended follow-up of 26 years, confirmed the presence of fibrils deposition. In 1993, a 32-year-old Caucasian man was admitted to our nephrology ward because of macroscopic hematuria. Renal function was normal. Kidney biopsy displayed an FGN with mesangial pattern. The patient was treated with lisinopril, titrated for blood pressure; the therapy was maintained during 26 years of follow-up. The yearly slope of estimated glomerular filtration rate was -3.17 mL/ min). Starting from March 2018, a rapid worsening of renal function was observed and proteinuria increased up to a nephrotic range. We planned a second renal biopsy to assess the cause of the rapid change of clinical course. The diagnosis of FGN on advanced sclerosis was made, and the severity of glomerular sclerosis. We report a case of FGN with an unusually benign clinical course, characterized by a slow progression to end-stage renal disease over a very extended follow-up time; thus, to better clarify the reason for renal function worsening, a second renal biopsy was performed. The persistence of fibrils deposition confirmed the initial diagnosis of FGN, and a histological pattern characterized by global glomerular sclerosis and interstitial fibrosis has been observed.